2011
DOI: 10.1007/s00040-011-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

Burial behaviour by dealates of the termite Pseudacanthotermes spiniger (Termitidae, Macrotermitinae) induced by chemical signals from termite corpses

Abstract: In order to maintain healthy colonies, termite workers dispose of the cadavers of dead nest mates by cannibalism, burial, or necrophoresis. However, when multiple reproductives found a new colony by pleometrosis, there are no worker castes at the early stages of the foundation to eliminate or isolate the corpses. In this study, we showed that in young pleometrotic colonies, reproductives of Pseudacanthotermes spiniger had the ability to perform this task. Because of the claustral conditions, and the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 30 publications
(37 reference statements)
2
60
0
Order By: Relevance
“…In Isoptera, the mechanism of undertaking elicitation has been recently studied in a fungus-growing termite, Pseudacanthotermes spiniger (Sjöstedt). The burial behavior in Pseudacanthotermes spiniger was triggered by a blend of indole, phenol, and fatty acids 19, which, at least in part, supported the “fatty acid death cue” hypothesis. In the eastern subterranean termite, Reticulitermes flavipes (Kollar), however, the “chemical vital sign” hypothesis could not be excluded based on our observation that workers showed an immediate response (< 15min) toward freshly killed nestmates 27.…”
Section: Death Recognition and Elicitation Of Undertaking Behaviormentioning
confidence: 58%
See 2 more Smart Citations
“…In Isoptera, the mechanism of undertaking elicitation has been recently studied in a fungus-growing termite, Pseudacanthotermes spiniger (Sjöstedt). The burial behavior in Pseudacanthotermes spiniger was triggered by a blend of indole, phenol, and fatty acids 19, which, at least in part, supported the “fatty acid death cue” hypothesis. In the eastern subterranean termite, Reticulitermes flavipes (Kollar), however, the “chemical vital sign” hypothesis could not be excluded based on our observation that workers showed an immediate response (< 15min) toward freshly killed nestmates 27.…”
Section: Death Recognition and Elicitation Of Undertaking Behaviormentioning
confidence: 58%
“…Most recently, an influx of studies have shown a complex series of undertaking behaviors in termites, including burial, avoidance, and cannibalism 7, 19-21. Cannibalism of the dead in termites was considered to be a mechanism of recycling nitrogenous nutrients47, 51, which is, in part, due to their nutritionally poor cellulosic diet52.…”
Section: Behavioral Responses Toward Corpsesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 51 compounds from the integument of a dead alate termite were extracted, and the majority contained fatty acid, phenol, and indol [13], [16]. The combination of the compounds was shown to trigger carcass-burying behavior in dealates of P. spiniger .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the global production of alates could not be measured. The fate of alates which never left the colony is not known with an absolute certainty, but they were probably eaten by workers or buried in cemeteries to avoid the proliferation of pathogens (Chouvenc et al, 2012). After 17 years of rearing, colonies of P. militaris were healthy and produced alates, but also died after they were transferred to another laboratory.…”
Section: Dispersal Flights In the Fieldmentioning
confidence: 99%